A Prospective Randomized Study to Assess the Feasibility and Compare the Acute Toxicity and Early Treatment Response in Locally Advanced Head-and-neck Patients Treated with Accelerated Fractionated Concurrent Chemoradiotherapy versus Conventional Chemoradiation - Chaparala, Shivani; Pandey, Laxman; Seam, Rajeev K.; Singh, Kaalindi; Bala, S. V. S.; Malik, Deepika; Acharya, Maitry; Inampudi, Prudhvi; Pandey, Apurva; Kadia, Kartik; Sherif, Jameel (Journal of cancer research and practice, 2025)
Abstract Background: To compare the acute toxicity and early treatment response in locally advanced head-and-neck cancer patients treated with accelerated fractionated radiotherapy with concurrent chemotherapy (AFCRT) versus conventional fractionation chemoradiation. Materials and Methods: Forty patients were randomized into two treatment arms. The prescribed dose to the high-risk planning target volume (PTV-HR) was 66-70 Gy at 2 Gy per fraction, 6 days a week. The intermediate-risk PTV (PTV-IR) received 59.4-63 Gy at 1.8 Gy per fraction, 6 days a week, and the low-risk PTV (PTV-LR) received 54-56 Gy at 1.69 Gy per fraction, 6 days a week for 33-35 fractions, respectively. In the control arm, the PTV-HR received 66-70 Gy at 2 Gy per fraction 5 days a week, the PTV-IR received 59.4-63 Gy at 1.8 Gy per fraction, 5 days a week, and the PTV-LR received 54-56 Gy at 1.69 Gy per fraction, 5 days a week for 33-35 fractions, respectively. Both arms received concurrent weekly chemotherapy at 40 mg/m2. Toxicity was assessed per Radiation Therapy Oncology Group (RTOG) toxicity Common Terminology Criteria for Adverse Events (CTCAE) ver. 5 weekly during radiotherapy, 6 weeks posttreatment, and at 3 months. Response to treatment was assessed at 6 weeks and 3 months using the Response Evaluation Criteria in Solid Tumors 1.1 criteria. Results: All the patients in both study groups completed their treatment. The average number of chemotherapy cycles administered in both groups was five. The total amount of chemotherapy received in both groups was similar (P = 0.249). After 3 months of follow-up, 14 (70%) patients in the study group and 13 (65%) patients in the control group showed a complete response in the local and regional areas (P = 0.898). Progressive disease was observed in 1 (5%) patient in the study group and 4 (20%) patients in the control group (P = 0.573). Severe (grade 3 or higher) acute side effects were similar in both groups. Late side effects observed between 3 and 6 months after treatment were also comparable. Interestingly, there was a significantly higher incidence of weight loss (>10%) in the control group (P = 0.020). Conclusion: AFCRT was safe and feasible. The study arm had higher overall response rates with comparable toxicity with conventional chemoradiation. The findings suggest that AFCRT is a promising treatment option.